Thermal energy storage technologies for concentrated solar power – A review from a materials perspective. (August 2020) - Palacios, A.; Barreneche, C.; Navarro, M.E.; Ding, Y.
Abstract: To compete with conventional heat-to-power technologies, such as thermal power plants, Concentrated Solar Power (CSP) must meet the electricity demand round the clock even if the sun is not shining. Thermal energy storage (TES) is able to fulfil this need by storing heat, providing a continuous supply of heat over day and night for power generation. As a result, TES has been identified as a key enabling technology to increase the current level of solar energy utilisation, thus allowing CSP to become highly dispatchable. This article aims to review different TES technologies that have been investigated and deployed over the past two decades. The review will give a comprehensive overview of TES technologies investigated, demonstrated and/or deployed in CSP plants with a specific emphasis on TES materials perspective. A thorough analysis will also be given on the state-of-the-art of the CSP technologies including commercial development and research innovation. An attempt is also made to use the information gathered along this review to postulate future technology evolution of CSP plants in terms of CSP configurations, TES technologies and location of CSP plants, and to assess the current and future role of TES in CSP field. Graphical abstract: Image 1 Highlights: Thermal energy storage is a key enable technology to increase the CSP installed capacity levels in the world. The two-tank molten salt configuration is the preferred storage technology, especially in parabolic trough and solar tower. By 2020, the plants without storage will be just 30% of the total installed capacity. Molten salt technology will be used in the 67% of the plants, followed by concrete, steam and packed bed. To increase TES deployement level, diversified alternatives must be found, specific for each CSP configuration requirements.